2002
DOI: 10.1002/hep.1840360610
|View full text |Cite
|
Sign up to set email alerts
|

Valine-alanine manganese superoxide dismutase polymorphism is not associated with alcohol-induced oxidative stress or liver fibrosis

Abstract: The role of genetic factors in the pathogenesis of alcohol‐induced liver disease (ALD) is receiving increasing attention. Recently, it has been reported that homozygosity for a valine to alanine substitution in the mitochondrial targeting sequence of manganese superoxide dismutase (Mn‐SOD) represents a risk factor for severe ALD. Because this mutation is postulated to modify enzyme transport into mitochondria, we have sought confirmatory evidence of this association in a larger group of patients and investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 22 publications
(1 reference statement)
0
18
0
Order By: Relevance
“…As the time of follow-up increased, the proportion of surviving patients with two Val-MnSOD alleles increased (27). This may explain why the genotypic repartition of alcoholic patients differed from control subjects when patients were studied at the time of the first liver biopsy showing cirrhosis (26,27), but not when blood samples were drawn at various times after diagnosis (40,41). In the present study, only patients with a documented HFE genotype were included.…”
Section: Discussionmentioning
confidence: 90%
“…As the time of follow-up increased, the proportion of surviving patients with two Val-MnSOD alleles increased (27). This may explain why the genotypic repartition of alcoholic patients differed from control subjects when patients were studied at the time of the first liver biopsy showing cirrhosis (26,27), but not when blood samples were drawn at various times after diagnosis (40,41). In the present study, only patients with a documented HFE genotype were included.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, an imbalance resulting in increased hydrogen peroxide formation and decreased detoxification may be a critical event for the initiation and progression of alcohol induced liver injury. With this said, however, studies performed in the UK with a larger cohort of alcoholic patients showed no association among the valine-alanine SOD2 polymorphism, alcohol-dependent markers of oxidative stress, and liver fibrosis [132]. Preliminary studies indicate that the SOD2 polymorphism may be correlated to fibrosis in NAFLD patients [133].…”
Section: Genetic Factors Determining the Pathobiology Of Fatty Liver mentioning
confidence: 91%
“…The increased oxidative stress could lead to greater risk of the development of NASH. The 1183 polymorphism does not infl uence susceptibility to alcohol-induced liver fi brosis or alcohol-induced oxidative stress ( 248 ).…”
Section: Sod2mentioning
confidence: 96%
“…A single study by Namikawa et al found a higher frequency of SOD2 genotype 1183-TT in 63 biopsy-proven NASH patients (frequency 0.841) compared with 150 healthy controls (0.680) ( 178 ). The minor C allele results in a valine-to-alanine change that may alter the helical structure of the mitochondrial targeting sequence, enhancing transport of manganese SOD to the mitochondria ( 248 ). The increased oxidative stress could lead to greater risk of the development of NASH.…”
Section: Sod2mentioning
confidence: 99%